2013
DOI: 10.1128/jvi.02549-12
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Costructure of the Simian Virus 40 T-Antigen Origin Binding Domain with Site I Reveals a Correlation between GAGGC Spacing and Spiral Assembly

Abstract: Polyomavirus origins of replication contain multiple occurrences of G(A/G)GGC, the high-affinity binding element for the viral initiator T-antigen (T-ag).The site I regulatory region of simian virus 40, involved in the repression of transcription and the enhancement of DNA replication initiation, contains two GAGGC sequences arranged head to tail and separated by a 7-bp AT-rich sequence. We have solved a 3.2-Å costructure of the SV40 origin-binding domain (OBD) bound to site I. We have also established that T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 101 publications
1
16
0
Order By: Relevance
“…Several co-crystal studies of the isolated OBD domain of LT (or E1) have revealed how individual OBD recognizes the PEN DNA sequences (Bochkareva et al, 2006; Enemark et al, 2002; Meinke et al, 2007; Meinke et al, 2013): individual OBDs do not interact with each other, but bind tightly to the PENs using the same interactions (Figure 5—figure supplement 1A,B). However, the OBDs in the hexameric LT131-oriDNA complex structure do not bind to the PENs and are disordered (Figure 5—figure supplement 1D).…”
Section: Discussionmentioning
confidence: 99%
“…Several co-crystal studies of the isolated OBD domain of LT (or E1) have revealed how individual OBD recognizes the PEN DNA sequences (Bochkareva et al, 2006; Enemark et al, 2002; Meinke et al, 2007; Meinke et al, 2013): individual OBDs do not interact with each other, but bind tightly to the PENs using the same interactions (Figure 5—figure supplement 1A,B). However, the OBDs in the hexameric LT131-oriDNA complex structure do not bind to the PENs and are disordered (Figure 5—figure supplement 1D).…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence that the SV40 T-ag OBD forms a spiral has been obtained from EM [85] and modeling studies [76]. Therefore, we examined the higher order structure that the JCV T-ag OBD adopts in crystal form 1.…”
Section: Resultsmentioning
confidence: 95%
“…The structure of the SV40 OBD bound to SV40 Site I was recently reported [76]. As in SV40, the two GAGGCs in the JCV Site I are separated by a 7 bp AT-rich sequence.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These structural studies have provided critical insights into the initiation process, such as establishing how the GAGGC pentanucleotides in the polyomavirus replication origins are recognized by the origin binding domains (OBD) within T-ag [ 27 32 ]. Related studies, conducted with the SV40 T-ag OBD, suggest that following site-specific DNA binding, the OBDs undergo rearrangements, including "spiral formation" [ 32 35 ]. Additional experiments have revealed the multiple roles played by the T-ag helicase domains during origin melting [ 36 38 ], oligomerization [ 39 , 40 ] and helicase activities ([ 39 , 40 ]).…”
Section: Introductionmentioning
confidence: 99%